Data Buildings: Sensor Feedback in Sustainable Design Workflows. (3rd January 2018) - Peters, Terri
Abstract : While ever more architects use digital simulations of energy and daylight to inform their designs, relatively few carry out post‐occupancy evaluations of their buildings. This, according to University of Toronto post‐doctoral researcherTerri Peters, is a missed opportunity. Presenting recent built examples of a variety of building types by three leading practices in the US and Denmark, she sets out how sensor‐derived feedback can not only assist future design decisions in terms of building performance, operating systems and use patterns, but also encourage more sustainable behaviour among building users.